2015
DOI: 10.1590/0037-8682-0055-2014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of tuberculosis in the State of Amazonas, Brazil

Abstract: 63www.scielo.br/rsbmt I www.rsbmt.org.br Revista da Sociedade Brasileira de Medicina Tropical 48(Suppl I):63-69, 2015http://dx.doi. org/10.1590/0037-8682-0055-2014 Review Article ABSTRACT Tuberculosis (TB) is one of the infectious diseases that contributes most to the morbidity and mortality of millions of people worldwide. Brazil is one of 22 countries that accounts for 80% of the tuberculosis global burden. The highest incidence rates in Brazil occur in the States of Amazonas and Rio de Janeiro. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
(10 reference statements)
1
8
0
7
Order By: Relevance
“…However, the incidence of tuberculosis-HIV co-infection was high in females, indicating a greater number of new HIV-positive women. These data support those of other studies conducted in Brazil that showed a higher incidence and prevalence of tuberculosis and HIV infection in males, as well as increased rates of tuberculosis-HIV co-infection, 3 , 14 which is influenced by genetic, environmental, and immunological factors and of which better understanding would lead to advances in diagnosis that would favor the development of new technologies and treatments for both diseases 15 …”
Section: Discussionsupporting
confidence: 87%
“…However, the incidence of tuberculosis-HIV co-infection was high in females, indicating a greater number of new HIV-positive women. These data support those of other studies conducted in Brazil that showed a higher incidence and prevalence of tuberculosis and HIV infection in males, as well as increased rates of tuberculosis-HIV co-infection, 3 , 14 which is influenced by genetic, environmental, and immunological factors and of which better understanding would lead to advances in diagnosis that would favor the development of new technologies and treatments for both diseases 15 …”
Section: Discussionsupporting
confidence: 87%
“…A região Norte do Brasil é considerada zona endêmica de doenças infectocontagiosas, como hanseníase, síndrome da imunodeficiência humana adquirida (AIDS), leishmaniose, malária, leptospirose, tuberculose e hepatite 7,8,9,10,11,12,13,14 . E, ainda, configura local de doenças reemergentes como cólera e febre tifoide 12,15 .…”
Section: Introductionunclassified
“…Tuberculosis remains a major challenge in the region and the historical series analyzed by Garrido et al (14) clearly shows a high mortality rate and a poor performance of the indicators of treatment success, which are affected by specific problems faced by the indigenous population and the growing human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) epidemic of. The main concern is the emergence of multidrug resistant M. tuberculosis, especially considering the frequent lack of access to timely diagnosis coupled with a high rate of noncompliance with treatment (14) .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The main concern is the emergence of multidrug resistant M. tuberculosis, especially considering the frequent lack of access to timely diagnosis coupled with a high rate of noncompliance with treatment (14) .…”
Section: Conflict Of Interestmentioning
confidence: 99%